2016
DOI: 10.1021/acs.langmuir.5b04354
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Elasticity of the Crude Oil–Brine Interface in Relation to Improved Oil Recovery

Abstract: Injection of optimized chemistry water in enhanced oil recovery (EOR) has gained much interest in the past few years. Crude oil-water interfaces can have a viscoelastic character affected by the adsorption of amphiphilic molecules. The brine concentration as well as surfactants may strongly affect the fluid-fluid interfacial viscoelasticity. In this work we investigate interfacial viscoelasticity of two different oils in terms of brine concentration and a nonionic surfactant. We correlate these measurements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 24 publications
5
103
1
Order By: Relevance
“…It was concluded that oil-brine interactions are dependant on the presence of natural surface active compounds in crude oil (both asphaltene and resin), as well as type and concentration of ions in brine. Similarly, it was shown that IFT of crude oil-brine interfaces is dependant on asphaltene content of crude oil as a function of monovalent and divalent cation (NaCl and MgCl 2 ) concentrations [175]. In a different work, the effect of different ions (Ca 2+ , Mg 2+ , SO 2− 4 ), as well as diluted and softened seawater on dynamic IFT of crude oil-brine interfaces was studied [176].…”
Section: Interfacial Tensionmentioning
confidence: 99%
“…It was concluded that oil-brine interactions are dependant on the presence of natural surface active compounds in crude oil (both asphaltene and resin), as well as type and concentration of ions in brine. Similarly, it was shown that IFT of crude oil-brine interfaces is dependant on asphaltene content of crude oil as a function of monovalent and divalent cation (NaCl and MgCl 2 ) concentrations [175]. In a different work, the effect of different ions (Ca 2+ , Mg 2+ , SO 2− 4 ), as well as diluted and softened seawater on dynamic IFT of crude oil-brine interfaces was studied [176].…”
Section: Interfacial Tensionmentioning
confidence: 99%
“…One of their fields of application is enhanced oil recovery (EOR) from petroleum reservoirs [1][2][3][4]. With sizes below 100 nm and high specific surface area, nanoparticles (NPs) are suitable for subsurface porous media applications since they can pass through the pore throats of porous media without blocking them and enhance oil recovery at relatively low volume concentrations [5,6] via wettability alteration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it can be concluded that NPs adsorption during these experiments led to significant reduction of calcite dissolution both in DIW and LSW. 4.…”
mentioning
confidence: 99%
“…Another probable explanation in which twice-diluted seawater influences the trapped oil mobilization is by considering the effect of the viscoelastic interface. It has been recently suggested that when the low saline solutions come in contact with the polar organic components of oil, a highly viscoelastic film will be formed [56,57]. It has also been hypothesized that the interactions between the charged surface and the ions in electrolyte will lead to creating an ionic structure along the interface, known as the electrical double layer (EDL) [34, 58,59].…”
Section: Figure 8 Proposed Chemical Interactions Between Oil/brine/hmentioning
confidence: 99%